1995
DOI: 10.1063/1.871235
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic Vlasov simulation of the toroidal Alfvén eigenmode

Abstract: A new simulation method has been developed to investigate the excitation and saturation processes of toroidal Alfven eigenmodes (TAE modes). The background plasma is described by a magnetohydrodynamic (MHD) fluid model, while the kinetic evolution of energetic alpha particles is followed by the drift kinetic equation. The magnetic tluctuation of n=2 mode develops and saturates at the level of 1.8X 10m3 of the equilibrium field when the initial beta of alpha particles is 2% at the magnetic axis. after saturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 16 publications
0
97
0
1
Order By: Relevance
“…Compared with previous works 4,5 where magnetic moments of alpha particles are set to be zero, the present work has an advantage that a more realistic alpha-particle distribution can be considered. A realistic alpha-particle distribution is really indispensable to the study of alpha-particle losses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with previous works 4,5 where magnetic moments of alpha particles are set to be zero, the present work has an advantage that a more realistic alpha-particle distribution can be considered. A realistic alpha-particle distribution is really indispensable to the study of alpha-particle losses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, theoretical and computational studies [3][4][5][6] have shown that wave trapping of resonant particles works as a saturation mechanism of a single TAE mode. It is, however, not clear that the wave-particle trapping works as the dominant saturation mechanism when a large number of TAE modes are destabilized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several hybrid simulation models have been constructed [11][12][13][14][15] to study the evolution of AE modes destabilized by energetic particles. In the MEGA code, the bulk plasma is described using nonlinear MHD equations, and the energetic ions are simulated with the δ f particle method.…”
Section: Simulation Modelmentioning
confidence: 99%
“…The hybrid simulation model for MHD and energetic particles 23,24,8 is employed in the MEGA code. Plasma is divided into bulk plasma and energetic ions.…”
Section: Simulation Modelmentioning
confidence: 99%